Pengaruh Aksesibiltas Jalan Lingkar Barat Tallasa City Terhadap Perubahan Pemanfaatan Guna Lahan di Kecamatan Tamalanrea - Noel Diaken Patandean; S. Kamran Aksa; Ilham Yahya (Fakultas Teknik Universitas Bosowa, 2021)
This study aims to determine the effect of land use change on the accessibility of the Tallasa City West Ring road in Tamalanrea District. As well as how big the impact of the accessibility of the West Ring Road Tallasa City on the socio-economic conditions of the community in Tamalanrea District, this research can be used as input regarding the relationship between the accessibility of road development and changes in land use. The variables used consist of four of them: (1) Accessibility, (2) Economic Activities, (3) Land Change, (4) City Development. The analytical method used is in the form of chi-square analysis, then a contingency test is used to draw conclusions, which is followed by a Likert scale scoring system as a parameter to determine the magnitude of the relationship between X and Y variables and simple linear regression analysis to find out what percentage of land changes that occur, especially in economic activity variables. . Furthermore, to determine the impact of the accessibility of the Tallsa City West Ring road on the social economic conditions of the community by using a qualitative descriptive analysis method The results of this study indicate that all variables have an influence on accessibility. And it shows that accessibility has an impact on land changes, especially economic activity, which automatically changes the economic conditions of the community along the corridor of the Tallasa City West Ring Road, Tamalanrea District.